The Tafsīr of the Qur’ān: The Stages of Documentation - Yasir Sulaiman Almuways (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2020)
This article briefly reviews the history of the Science of Tafsīr in relation to the stages of the documentation of the Tafsīr of the Qur’ān from the time of our Prophet Muḥammad ṣallallāhu ʿalyh wa sallam until the time it was officially documented. From then until now, different perspectives have existed in relation to how the Tafsīr of the Qur’ān has been approached. Therefore, this article provides an introductory and historical overview on relevant terminology; different sources, schools, and types of Tafsīr; as well as the different characteristics of Tafsīr stages. An understanding of these aforementioned points will provide the key to answering the research question posed here: What are the stages of the documentation of the Tafsīr of the Qur’ān?